(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate this problem incidence and severity, and to control this problem. Study Design: Descriptive / cross-sectional study Place and Duration of Study: This study was conducted at the Department of General Surgery, Khalifa Gul Nawaz Teaching hospital Bannu from June 2015 to June 2016. Materials and Methods: Study was conducted on 42 patients aged between 20-52 years with symptomatic gall stone disease. Patients more than 15 years of age having symptomatic gall stone disease were included in the study. A proforma was designed for Operative time, CO2 pneumoperitoneum pressure and shoulder tip pain and the results were analyzed on SPSS 23. Results: The mean age was 33.8 years and age range was 20-52 years. There were 7 males and 35 females and male to female ratio was 1:5. The mean operative time was 55 minutes and the mean pressure pneumoperitoneum was 12mmHg. The incidence of shoulder tip pain was 33.3%. The shoulder tip pain was significantly more in patients operated with high pneumoperitoneum pressure. Conclusion: There were significantly more patients who experienced shoulder tip pain when the CO2 pneumoperitoneum pressure was more and the severity was also more as compared to low pressure.